Matters of the heart - Abd Razak, Dzulkifli (2011)
HIGHER Education Minister Datuk Seri Mohamed Khaled Nordin gave his annual address to a gathering of administrators, academics and students last week with a reminder that we are now in the second phase of the Ministry's Strategic Plan to transform the milieu of higher education in Malaysia. It is now about “strengthening and enhancing” after “lying the foundation”.